Crips - Crash Recognition & Injury Prevention in alpine ski racing - Spitzenpfeil, P.; Huber, A.; Waibel, K. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: The project "Crash Recognition & Injury Prevention Systems (CRIPS)" tries to find, prove and compare different solutions in a multidimensional way to improve safety in alpine ski racing. Safety has become one of the main problems in alpine ski racing. During the past years many serious accidents occurred in the Alpine World Cup sometimes with fatal consequences for the racers (e.g. Lanzinger). As recent studies have shown, ACL ruptures are playing a major role among the minor injuries not only in racing but also in leisure time skiing since many years (Bambach et al., 2008). In the rehabilitation of ACL ruptures, leg braces are successfully used to stabilize the knee and to avoid re-ruptures (Sterett et al., 2006). Some studies on the prophylactical use of knee braces have been done in the 80s and early 90s (e.g. Martinek et al. 1999) regarding them as "inadequate" and "not sufficient. The development of construction and materials however, may lead to better solutions. Therefore the aim of the study was to prove the influence of leg braces on performance and comfort and developing concepts for innovative solutions.